Sharing Pengetahuan dan Informasi Terhadap Pentingnya TOEFL Untuk Siswa-Siswi SMAN 4 Pematang Siantar - Silaban, Lusia Pebriyani; Simanjuntak, Gina Wijaya; Manurung, Agatha Olivia Putri; Herman, Herman; Sirait, Jumaria; Batubara, Junita; Niswa, Khairun (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
TOEFL (Test of English as a Foreign Language) has now become a main requirement for career advancement or continuing higher level education. Many schools and campuses have a vision to prepare their students from an early age to be ready to enter the world of work by requiring TOEFL as a graduation requirement. This socialization aims to increase knowledge and information about TOEFL for class XII IPA 2 SMAN 4 Pematang Siantar, totaling 31 students. This activity was carried out using a lecture method by the socialization team using power points, a question and answer session, as well as discussions about TOEFL and its benefits. The location of this socialization activity was Jalan Pattimura No. 1, Pahlawan, East Siantar District. Carried out on November 20 2023. In writing this research journal used a qualitative descriptive method in collecting data. The results of this socialization activity can be concluded that students understand the socialization material. This can be seen from the structured delivery of material and the social activity schedule that is prepared so that it can help students focus more on understanding the material. Apart from that, several questions in the question and answer session show that the material can be absorbed by students well.